Penerapan Model Pembelajaran Guided Discovery Dengan Menggunakan Media Mindjet Mind Manager Untuk Meningkatkan Aktivitas dan Hasil Belajar Kimia Siswa Kelas X IPA SMA Bahrul Maghfiroh Malang - Wilyati Agustina Bangun; Moh. Zaini (IKIP Budi Utomo Malang, 2016)
Difficulties faced by students about the chemistry lesson, causing students to be passive and low impact on student learning outcomes. Therefore we need a method and model of teaching, so that students are able to discover the concepts, principles through his own mental process. The learning model used is the Guided Discovery, -which give maximum freedom to the students to develop creative thinking and motor power, while the role of the teacher is limited. This learning model utilizes computer media with Mindjet program mindmanagerr 9, which is connected to the power point and macro flash, making it easier for students to show the concepts of Chemistry abstract becomes more concrete.